Validity and reliability of the Turkish version of the HLS-EU-Q6 questionnaire - Müjdat YEŞİLDAL (BMC Public Health)
Abstract Background Health literacy plays an important role in the effectiveness of health services by affecting individuals’ ability to access, understand, and use health information. Many people in Turkey have limited health literacy. This study aimed to determine the psychometric validity and reliability of the Turkish version of the HLS-EU-Q6. Methods This psychometric study used a cross-sectional design and was conducted with 475 Turkish adults between January and March 2024. The adaptation followed internationally accepted guidelines, including translation, synthesis, back-translation, expert panel review, piloting, and finalization. Content validity was assessed using the Content Validity Index (CVI). The sample was randomly divided into two independent subsamples for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability analyses included Cronbach’s alpha, McDonald’s omega, composite reliability (CR), average variance extracted (AVE), and item discrimination indices. Results In the EFA group, the mean age was 28.89 ± 9.44 years, and 63.4% were female. The CFA group’s mean age was 28.76 ± 10.05 years, and 67.3% were female. According to the TR-HLS-EU-Q6, problematic health literacy was identified in 77.5% of participants in the EFA group and 73.8% in the CFA group. Exploratory factor analysis supported a unidimensional factor structure with loadings ranging from 0.664 to 0.853. Confirmatory factor analysis confirmed acceptable model fit (χ²/df = 2.61, RMSEA = 0.06, SRMR = 0.06, TLI = 0.92, GFI = 0.96). Cronbach’s alpha and McDonald’s omega coefficients were 0.82 and 0.84, respectively, demonstrating high internal consistency. The AVE was 0.59, supporting convergent validity. Discriminant analyses showed significant item discrimination between high- and low-scoring groups (p < 0.001). Conclusions The Turkish version of HLS-EU-Q6 consistently showed acceptable psychometric reliability and validity characteristics.